Genetic parameter estimates for birth and weaning weights, pre-weaning daily weight gain and three type traits for Charolais beef cattle in Spain - El-Saied, U.M.; de la Fuente, L.F.; Rodríguez, R.; San Primitivo, F. (Spanish Journal of Agricultural Research, 2006)
Genetic parameters were estimated using REML in a multiple-trait animal model including genetic direct and maternal effects for birth and weaning weights, pre-weaning daily weight gain and three linearly scored traits (muscularity, skeletal size and general appearance) in 3,428 Charolais calves. The three complex type traits were scored at weaning on a nine-point scale. Fixed effects considered were herd-year-season of birth, sex of the calf and parity number of the dam. The fixed effect of weaning season and the linear covariate of age at weaning were considered for all variables except for birth weight. All fixed effects contributed significantly (P < 0.001) to variations in all traits except for the effect of weaning season which was not significant for the general appearance score. The percentage of variance explained by the model averaged 50.74% for the considered traits. Average birth and weaning weights and pre-weaning daily weight gain were 42.95, 278.21 and 1.11 kg, respectively, while muscularity, skeletal size and general appearance scores averaged 5.33, 5.19 and 5.36, respectively. Direct heritability estimates were 0.36, 0.36, 0.22, 0.50, 0.52 and 0.52 for the six traits, respectively. The corresponding maternal heritabilities were 0.37, 0.32, 0.18, 0.18, 0.15 and 0.13, respectively. Direct genetic correlations among these traits varied from low and negative (0.11) between birth and weaning weights to extremely high and positive (0.95) between muscularity and skeletal size scores. Type traits can be effectively used to improve the efficiency of beef production for Charolais calves in Spain.